Thigh magnetic resonance imaging for the evaluation of disease activity in patients with idiopathic inflammatory myopathies followed in a single center. Issue 4 (9th June 2016) - Barsotti, Simone; Zampa, Virna; Talarico, Rosaria; Minichilli, Fabrizio; Ortori, Simona; Iacopetti, Valentina; D'ascanio, Anna; Tavoni, Antonio Gaetano; Bombardieri, Stefano; Mosca, Marta; Neri, Rossella
ABSTRACT: Introduction : In patients with idiopathic inflammatory myopathies (IIM), magnetic resonance imaging (MRI) has been proposed as a useful tool for diagnosis and follow‐up. It may identify muscle inflammation (edema) and fatty infiltration for evaluation of disease activity and damage. Little information is available on the role of MRI in assessment of large cohorts of adult patients with IIM. Methods : Fifty‐one patients underwent MRI of the thigh muscles, laboratory tests, and clinical evaluation, including Physician Global Assessment (PGA) of myositis activity and the Manual Muscle Test 8 (MMT8). Results : Muscle edema correlated significantly with creatine kinase values ( P = 0.017) and PGA ( P < 0.001). A significant correlation between edema and MMT8 values ( P = 0.025) was observed when patients with muscle fatty infiltration were excluded. With respect to clinical diagnosis, the sensitivity of MRI was 92.3%, and specificity was 83.3%. Conclusions : MRI appears to provide additional information that complements clinical and biochemical examinations. Muscle Nerve 54 : 666–672, 2016